PENGARUH TEKANAN WAKTU DAN BEBAN KERJA TERHADAP PENDETEKSIAN KECURANGAN DENGAN PENGALAMAN KERJA SEBAGAI PEMODERASI - Shanti, Yunita Kurnia; Sih Kusumawardhany, Susi (ITB AAS Indonesia Surakarta, 2025)
This study aims to test and obtain empirical evidence regarding the effect of time pressure and workload on fraud detection moderated by work experience at the South Jakarta Public Accounting Firm. This type of research is quantitative with the sampling method is the Convenience sampling method, obtained 66 respondents who were used as research samples, so that the total observation was 66 samples. The data analysis method used SPSS version 24 along with the MRA test. Based on the data analysis that has been carried out, it shows that partially time pressure has a negative effect on fraud detection, and workload has no effect on fraud detection. Simultaneously, time pressure and workload have a significant effect on fraud detection. The results of the MRA test show that work experience is unable to moderate the effect of time pressure and workload on fraud detection, meaning that work experience weakens the effect of time pressure and workload on fraud detection.